Spectrum-aware shared protection (SASP) algorithm for cognitive radio networks - Rajavel, S. Esakki; Aruna, T.; Devaraj, S. Allwin (International Journal of Engineering and Technology, 2018)
Cognitive radio (CR) has become a key technology for addressing spectrum scarcity. In CR networks, spectrum access should not interfere the incumbent networks. Due to the requirement above, common control channel approaches, which are widely used in traditional multichannel environments, may face serious CR long-time blocking problem and control channel saturation problem. Although channel-hopping-based approaches can avoid these two problems, existing works still have significant drawbacks including long time-to-rendezvous, unbalance channel loading, and low channel utilization. This paper tends to the issue of range mindful survivable methodologies with disappointment likelihood limitations under static activity in adaptable transfer speed optical systems. The joint disappointment likelihood amongst essential and reinforcement ways must be beneath the most extreme fair joint disappointment likelihood for each activity request. It creates whole number direct program (ILP) models for committed way security and shared-way assurance with a specific end goal to limit the aggregate number of recurrence spaces expended, and furthermore propose a range mindful devoted insurance (SADP) calculation and a range mindful shared security (SASP) calculation. This demonstrates the ILP show arrangements devour least number of recurrence spaces, however prompt higher normal joint disappointment likelihood contrasted with the SADP and SASP calculations. In addition, both the SADP and SASP calculations accomplish a superior execution as far as aggregate number of recurrence openings expended when contrasted with a customary devoted way insurance calculation and an ordinary shared-way assurance calculation, separately, however prompt higher normal joint disappointment likelihood.